PERBANDINGAN IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DI INDONESIA DAN MALAYSIA: STUDI LITERATUR - Achmad Firdaus; Dewi Luthfiyah; Mufarikha; M. Debi Wananda; M. Ridlwan Al-Khoir (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2025)
This study aims to comparatively analyze the implementation of multicultural education in the education systems of Indonesia and Malaysia. This study is motivated by the importance of multicultural education in fostering an inclusive and tolerant society amidst the cultural, religious, and ethnic diversity of both countries. The method used is a literature study with a qualitative descriptive approach through the analysis of various sources such as journals, education policies, and official government documents. The results show that Indonesia implements multicultural education integratively by incorporating character, religious, and social values into various subjects and school activities, both in formal and non-formal institutions. Meanwhile, Malaysia implements multicultural education more systematically through the National Education System (Sysdik Kebangsaan) with two models: integrative and separate, supported by national policies and teacher training. Although both countries are committed to diversity, Malaysia excels in terms of policy support and implementation systems. This study recommends that Indonesia strengthen its policies and teacher training so that multicultural education can be implemented more effectively and comprehensively.